PENGARUH MIKROORGANISME LOKAL REBUNG DAN PLANT GROWTH PROMOTING RHIZOBACTERIA TERHADAP NITROGEN TANAH TOTAL, POPULASI BAKTERI DAN PRODUKSI KACANG TANAH (Arachis hypogaea L) - Dwi Mawar Purwaningtyas; Yulia Nuraini (Jurnal Tanah dan Sumberdaya Lahan, 2022)
The aim of this study was to explore the effect of local microorganism (MOL) bamboo shoots and plant growth-promoting rhizobacteria on total nitrogen soil, total bacterial population and groundnut production. The study was carried out in March-November 2021 at the Jatimulyo Experimental Field, and Laboratory of Soil Chemistry and Biology, Faculty of Agriculture, Brawijaya University. The study used a randomized block design consisting of nine treatments with three replication. The results showed that the application of local microorganisms and plant growth-promoting rhizobacteria (MOL and PGPR) did not show significantly different results in the total soil nitrogen, but the total soil nitrogen increased by 16% of control and the total bacterial population in the soil. The application of MOL and PGPR resulted in a total bacterial population (5.03 x 106 CFU mL-1 ) which was significantly different between treatments (58% of control). The application of MOL and PGPR did not show a significantly different in groundnut production but increased groundnut production from 1.2 t ha-1 to 2.4 t ha-1 (74% of control). The best treatment was M2P1 (55.5 L ha-1 MOL and 27.7 L ha-1 PGPR), with the most optimal content of microorganisms to support the growth and development of groundnut.